Potensi Biogas Dari Sampah Organik Kampus Dengan Biodigester Sistem Kering - Lilya Irsianti Fadlilah; Aryo Sasmita; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The volume of waste generation is increasing along with the increasing consumption of the people of the University of Riau every day, where the organic waste material that is processed is 137.16 Kg/day which has an impact on the accumulation of waste, especially at the TPS of Riau University. Therefore, an alternative waste management is needed to reduce the volume of waste that will be transported to the landfill by processing organic waste into biogas through biodigester technology. This study aims to design an appropriate anaerobic digester reactor system to treat the organic waste produced. By using the method of collecting and processing secondary data, then analyzed economically using the NPV (Net Present Velue) method. From the results of the economic analysis carried out, it was found that the selected digester was a dry system digester with an NPV value of Rp. 27,384,143. The dimensions for the biocel reactor are obtained with the following description; length 3 m, width 3 m, height 1,266 m and the number of reactors as many as 15 units and the amount of biogas production per day is 5,706 m3/day. Keywords: Organic Waste, Biogas, Biocel Reactor, NPV (Net Present Velue)